PTU-098 The UK inflammatory bowel disease audit: key findings from the inpatient experience questionnaire. (28th May 2012) - Bodger, K; Arnott, I; Down, C; Driscoll, R; Protheroe, A; Roughton, M
Abstract : Introduction: The UK IBD Audit seeks to improve the quality and safety of care for IBD patients throughout the UK by auditing individual patient care and provision and organisation of IBD service resources. The inclusion of an inpatient experience questionnaire in the 3rd round of the audit provided the opportunity to obtain direct patient feedback regarding hospital care. Methods: Teams at participating sites were required to audit a consecutive sample of inpatients with UC and CD. Completion of local clinical data entry for each case triggered the generation of a patient survey comprising a self-completed questionnaire containing items taken from the National Inpatient Survey questionnaire (Picker Institute) with supplementary questions specific to IBD. Aggregated results are presented for all respondents. Results: Response rate : 33% (data for 2028 adults and 166 children). Results presented as adults [children] where appropriate. Overall care rated as only fair by 7% [6.7% children] and poor by 2.9% [0%]. Overall satisfaction correlated most strongly with rating of how well doctors and nurses worked together. Composite scores across six domains of acute adult care were comparable across all countries (no national differences). Scores for CD were lower than UC in several domains. Scores for consistency and coordination of care and nursing were relatively low compared to general adult inpatients (National Inpatient Survey, 2009). Only 60% of adults [76% children] reported a visit from a specialist nurse. Hospital food : Rated as poor by 20% [11%]; "Too little" food provided was reported by 15% [16%]; "Never" suited to dietary needs by 15% [8%]. No dietician visit in 59% [26%]. Pain management : "Ever in pain?" 85% [83%]; pain "usually severe" 52% [52%]; analgesic medication "not enough" 16% [12%]. At least 1 in 10 reported sub-optimal aspects of discharge information such as lack of information about drug side effects, the danger signs to watch for or how to manage their condition after going home. Conclusion: There are many positive findings from the UK IBD inpatient survey—over ¾ of adults and children rated care as "very good" or "excellent". There are areas for potential improvement. Patients place a strong value on co-ordinated care from experienced staff. Greater provision and involvement of IBD nurses at ward level could play a key role in promoting excellent inpatient care. All admitted IBD patients should receive input from specialist multidisciplinary teams experienced in managing these complex disorders. Competing interests: None declared.